Analisis Pengelolaan Badan Usaha Milik Desa Mandiri Desa Kassiloe Kecamatan Labakkang Kabupaten Pangkep - Wahyu Karunia Galib (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2017)
Subdistrict of Pangkep Regency to see the management process of BUM Desa Mandiri so that it will generate the original income of the village along with factors influencing the management of BUM Desa Mandiri Desa Kassiloe. The research method used is qualitative research method by describing and explaining the result of research in written form. Data collection is done using literature study techniques, observation, interviews, and search data online. This research describes the management process of BUM Desa Mandiri consisting of management organization, capital, business activity, profit sharing and supervision. The factors that affect the management of BUM Desa Mandiri, among others, supporting factors such as policies on village BUM and infrastructure facilities. Inhibiting factors such as human resources and supervisors